ANALISA RESCHEDULE REPAIR KM STU MENGGUNAKAN METODE CRITICAL CHAIN PROJECT MANAGEMENT - Sari, Zulia Wulan; Dira Ernawati (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2024)
PT XYZ is the largest shipyard company in Indonesia. As the largest shipyard, PT XYZ is required to PT XYZ is the largest shipyard company in Indonesia. As the largest shipyard, PT XYZ is the largest shipyard company in Indonesia. As the largest shipyard, PT XYZ is required to complete new shipbuilding and repair projects quickly, in accordance with the agreement stated in the contract agreed between the shipowner or his representative and the shipyard. In this case, project scheduling planning plays a very important role to ensure that each stage of work can be completed efficiently and on time. However, the schedule designed from the start is not always fully aligned with the implementation in the field, so that the work has the potential to be delayed from the specified time. The delay also occurred in the KM STU repair project carried out by PT XYZ. Therefore, a reschedule was carried out using the Critical Chain Project Management method. By implementing the CCPM method, the results showed that the project duration was 13 days with an additional project buffer of 3.5 days and a cost of IDR 266,000,000 which was the same as the normal duration or initial condition. However, if the buffer time in the CCPM duration is fully used, the total cost obtained will increase to IDR 304,080,000 or around 14.3% of the CCPM cost without a buffer. Meanwhile, worker productivity by implementing the Critical Chain Project Management method has increased compared to before. Previously, the average worker productivity was 27.45/mandays. Then after implementing the CCPM method, the average worker productivity became 54.89/mandays. Based on the results of the study, it can be seen that the Critical Chain Project Management method is more effective and efficient than the previous method. So that the results of this study can be used by the company as a reference in planning the next repair project schedule.